FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PERUSAHAAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Yolanda Christanto; Magdalena Nany (widya balina, 2025)
Due to the fact that it exploits legal gaps (gray areas) in tax rules and regulations, tax avoidance is classified as a valid and non-violating activity, despite the fact that the government does not want it. This study aims to gather factual information about the relationship between tax avoidance and firm size, sales growth, capital intensity, and profitability. 111 data points were gathered from 37 banking companies that were listed on the Indonesia Stock Exchange between 2020 and 2022. The gathered data was examined using multiple regression analysis at a 5% significance level. It was discovered that there was no discernible relationship between tax evasion and profitability, capital intensity, firm size, or sales growth.